2017
DOI: 10.1021/acs.chemmater.7b03735
|View full text |Cite
|
Sign up to set email alerts
|

Morphology Evolution and Spatially Selective Functionalization of Hierarchically Porous Silica Nanospheres for Improved Multidrug Delivery

Abstract: Hierarchically porous materials are believed one of the most promising matrix materials due to their unique multimodal pore structures and great application potentials in catalysis, separation, and biomedicine. In this article, a series of hierarchically porous silica nanospheres with adjustable morphologies and pore structures/sizes has been successfully developed by controlling the electrostatic interaction-induced interfacial self-assembly behaviors between anionic block copolymer polystyrene-b-poly­(acryli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 39 publications
(53 reference statements)
0
18
0
Order By: Relevance
“…It has been also found that the nature of silica precursors, solvents or co-solvents, catalysts, and, finally, pH of the reaction medium also affect the MSN structure. Spherical worm-like MSNs with mesopores or hierarchical porous structures, including hollow [ 16 , 17 , 18 ], yolk-shell, stellate nanoparticles (NPs) [ 19 ] have been synthesized by suitably tuning SDA, precursors nature, concentration, reaction condition such as duration and temperature of hydrolysis and condensation or application of post-synthetic treatments.…”
Section: Introductionmentioning
confidence: 99%
“…It has been also found that the nature of silica precursors, solvents or co-solvents, catalysts, and, finally, pH of the reaction medium also affect the MSN structure. Spherical worm-like MSNs with mesopores or hierarchical porous structures, including hollow [ 16 , 17 , 18 ], yolk-shell, stellate nanoparticles (NPs) [ 19 ] have been synthesized by suitably tuning SDA, precursors nature, concentration, reaction condition such as duration and temperature of hydrolysis and condensation or application of post-synthetic treatments.…”
Section: Introductionmentioning
confidence: 99%
“…The hollow porouss phere is as pecial functional material, due to its unique structure, whichh as become ap romising and attractive material for chemical catalysis, nanoreactors, drug delivery vehicles, and energy conversion and storage. [40][41][42][43][44][45][46] Nano-sized hollow porouss pheres can adjust the volume change in the catalytic process to increaset he structural stability.T herefore, hollow porousM nFe 2 O 4 spheres were prepared in presentw ork to obtain excellent HER and OER performance, and it was further optimized by growingo nt he surfaceo fb iochar.T he elm moneyh as meritorious physical and chemical properties because of its unique structure and natural carbon skeleton, which could afford many natural pores and facilitate the rapid transfer of electrolytes, and is beneficialt of aster release of air bubbles. [47][48][49] In this paper, MnFe 2 O 4 hollow porous sphere ande lm-money-derived biocharc omposites (MnFe 2 O 4 / BC) are obtained as dual-functional electrocatalysts for overall water decomposition.…”
Section: Introductionmentioning
confidence: 99%
“…The hollow porous sphere is a special functional material, due to its unique structure, which has become a promising and attractive material for chemical catalysis, nanoreactors, drug delivery vehicles, and energy conversion and storage [40–46] . Nano‐sized hollow porous spheres can adjust the volume change in the catalytic process to increase the structural stability.…”
Section: Introductionmentioning
confidence: 99%
“…[95] Our group has developed a series of dualmodal mesoporous silica nanoparticles based on the this co-templating system (Figure 10A). [95][96][97][98] During the cotemplating process, the bridging effect of CTAB is important since single PS-b-PAA lacks sufficient interaction with the backbone species, the hydrolyzed silane. In slightly basic aqueous solution, the hydrophilic PAA blocks could couple with CTAB micelles via electrostatic Coulomb force to form F I G U R E 1 0 (A) Formation of the dual mesoporous materials templated by PS-b-PAA/CTAB composite micelle aggregates.…”
Section: Ionic Bcp With Ionic Surfactantmentioning
confidence: 99%